Changes in the axial orientation of the zygapophyseal joint in the subaxial cervical spine from childhood to middle-age, and the biomechanical implications of these changes. (October 2017) - Chen, Mao-Yu; Liu, Yu-Tse; Hsu, Wen-Hsing
Highlights: Cervical spine facet orientation (FO) varies from childhood to middle-age. The level of greatest external rotation varies significantly with aging. C3/4 and C4/5 external rotation decreases with aging. The C5/6 level is the level of greatest external rotation at any age. C6/7 FO external rotation increases to young adulthood, then decreases. Abstract: The objective of this study was to investigate the effect of age on facet orientation (FO) of the cervical spine during development, maturation, and degeneration. Computed tomography (CT) data of the cervical spine of 131 subjects without pathology of the cervical spine were analyzed. Subjects were categorized as: pediatric (n = 36, 8–16 years old), young adult (n = 33, 18–24 years old), and middle-age (n = 62, 40–59 years old). Serial CT scans were reconstructed by image processing. The FO in the axial plane was measured bilaterally at each vertebral level from C3/4 to C6/7. Differences in FO were analyzed between the 3 groups. The degree of external rotation of FO significantly decreased at C3/4 and C4/5 with increasing in age, and maximum external rotation was observed at C5/6. The external rotation at C6/7 increased from pediatric to young adulthood, but decreased from young adults to middle-aged adults. The dominant external rotation was seen in C4/5 and C5/6 in the pediatric age group, C5/6 and C6/7 in young adults, and C4/5 and C5/6 in middle-aged adults. These results lead us to conclude that FO in the axial plane exhibits significant differences with age. The degree of external rotation with respect to FO at each vertebral level is comparable to changes in cervical spinal dynamics with age. Hence, FO in the axial plane is a biomechanical parameter that can be used to assess changes in the cervical spinal during maturation and degeneration.